Felicidade na ruralidade: a contribuição do bem-estar subjetivo na permanência do agricultor familiar ao campo - Berghauser , Neron Alipio Cortes (2023)
This descriptive study investigated as the happiness factors that contribute to the permanence of the farmer in the countryside. Happiness, also expressed as subjective well-being, as a genuinely human feeling, results from the perception of several external and internal conditions to the individual and can contribute greatly to growth as a social being. It can be produced by experimenting with certain mental states, such as joy, health, love, serenity, contentment, safety, satiety, or even sexual pleasure. Happiness is also conceived as the degree in which a person considers the totality of his current life positively and experiences affections of a pleasant type. The research has a crosscut in 2022 without considering the evolution of data over time. The population researched was composed of 121 family farmers from the western region of the state of Paraná. The collection instrument was a structured interview, adapted from FIB (gross internal happiness indicator), a model proposed for the assessment of the degree of happiness of a social group, which contains 9 dimensions: psychological well-being; Health; Education; Culture and traditions; Use of time; Government; Relations with the community; Ecological and environmental aspects; and standard of living. Conceived as an alternative means for assessing the degree of development of a nation, by inserting social and behavioral elements, FIB proposes to broaden the look at the quality of life and well-being of a particular population. The results pointed out that there is a strong presence of personal or individual aspects in both the assessment of happiness and permanence, compared to the others. They have indicated that there are also priority aspects related to their well-being on the property that need to be attended to those of a general nature. The dimensions of happiness, health, education, and standard of living received the highest positive scores while those of collective bias such as government, community relations, and environmental issues were those of the lowest positive scores evaluated.